Correlations between peripheral parasite load and common clinical and laboratory alterations in dogs with visceral leishmaniasis - Torrecilha, R. B.P. [UNESP]; Utsunomiya, Y. T. [UNESP]; Bosco, A. M. [UNESP]; Almeida, B. F. [UNESP]; Pereira, P. P. [UNESP]; Narciso, L. G. [UNESP]; Pereira, D. C.M. [UNESP]; Baptistiolli, L. [UNESP]; Calvo-Bado, L.; Courtenay, O.; Nunes, C. M. [UNESP]; Ciarlini, P. C. [UNESP] (Elsevier, 2016)
Intensity of peripheral parasite infection has an important role in the transmission of Leishmania spp. from one host to another. As parasite load quantification is still an expensive procedure to be used routinely in epidemiological surveillance, the use of surrogate predictors may be an important asset in the identification of dogs with high transmitting ability. The present study examined whether common clinical and laboratory alterations can serve as predictors of peripheral parasitism in dogs naturally infected with Leishmania spp. Thirty-seven dogs were examined in order to establish correlations between parasite load (PL) in multiple peripheral tissues and common clinical and laboratory findings in canine visceral leishmaniasis (CVL). Quantitative polymerase chain reaction was employed to determine PL in conjunctival swabs, ear skin, peripheral blood and buffy coat. Additionally, a series of hematological, biochemical and oxidative stress markers were quantified. Correlations between net peripheral infection and severity of clinical alterations and variation in laboratory parameters were assessed through a new analytical approach, namely Compressed Parasite Load Data (CPLD), which uses dimension reduction techniques from multivariate statistics to summarize PL across tissues into a single variable. The analysis revealed that elevation in PL is positively correlated with severity of clinical sings commonly observed in CVL, such as skin lesions, ophthalmic alterations, onycogriphosis, popliteal lymphadenomegaly and low body mass. Furthermore, increase in PL was found to be followed by intensification of non-regenerative anemia, neutrophilia, eosinopenia, hepatic injury and oxidative imbalance. These results suggest that routinely used clinical and laboratory exams can be predictive of intensity of peripheral parasite infection, which has an important implication in the identification of dogs with high transmitting ability.
Keywords: Biochemistry; Canis lupus familiaris; Hematology; Leishmania spp; Oxidative stress; Principal components analysis